2020
DOI: 10.1002/ehf2.12792
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent hospitalizations are associated with increased mortality across the ejection fraction range in heart failure

Abstract: Aims The proportion of patients hospitalized for heart failure (HF) with preserved left ventricular ejection fraction (LVEF) is rising, but no approved treatment exists, in part owing to incomplete characterization of this particular HF phenotype. In order to better define the characteristics of HF phenotypes in Finland, a large cohort with 12 years' follow-up time was analysed. Methods and results Patients diagnosed between 2005 and 2017 at the Hospital District of Southwest Finland were stratified according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
23
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 29 publications
(109 reference statements)
7
23
1
Order By: Relevance
“…In our study, HFpEF accounted for 87.8% of all HF patients included, while HFmrEF and HFrEF accounted for 4.5% and 7.5% respectively. The prevalence of HFmrEF 4.5% in our study was muchlower thanin other studies(16%,24% or 17%) [7][8][9].Previous studies were mostly based on the statistical results of patients with HF, or registered in hypertension, HF centers and other related data [10][11][12]. In contrast, this study was on inpatients of geriatrics department, so it is much more asymptotic to the incidence of HF in the elderly population, and will be more conducive to reminding geriatricians of identifying HF patients, and following up analysis on HFpEF patients with a large proportion, and exploring more factors affecting heart function to further guide the clinical treatment of HFpEF [5].The mean age of HF patients included was 78.28, higher than those reported in other studies [5],which could be explained by the fact that our patients were enrolled from the geriatric department of a hospital where usually older patients are admitted.Previous studies including older patients showed a higher frequency of HFpEF [13].…”
Section: Discussioncontrasting
confidence: 65%
“…In our study, HFpEF accounted for 87.8% of all HF patients included, while HFmrEF and HFrEF accounted for 4.5% and 7.5% respectively. The prevalence of HFmrEF 4.5% in our study was muchlower thanin other studies(16%,24% or 17%) [7][8][9].Previous studies were mostly based on the statistical results of patients with HF, or registered in hypertension, HF centers and other related data [10][11][12]. In contrast, this study was on inpatients of geriatrics department, so it is much more asymptotic to the incidence of HF in the elderly population, and will be more conducive to reminding geriatricians of identifying HF patients, and following up analysis on HFpEF patients with a large proportion, and exploring more factors affecting heart function to further guide the clinical treatment of HFpEF [5].The mean age of HF patients included was 78.28, higher than those reported in other studies [5],which could be explained by the fact that our patients were enrolled from the geriatric department of a hospital where usually older patients are admitted.Previous studies including older patients showed a higher frequency of HFpEF [13].…”
Section: Discussioncontrasting
confidence: 65%
“…The baseline characteristics of patients in the current study were in line with other studies evaluating the relationship of recurrent HFHs on mortality or re-admissions following incident HFH. 1,12,14,18 The results of this study should be interpreted in light of some limitations. First, our analysis included only patients with a 4 year clean period, which is reasonable to assume as the study identified actual first HFH.…”
Section: Discussionmentioning
confidence: 91%
“…Aside from clinical characteristics and presentation, a few discrepancies are related to the outcome and mode of death of this group: although some studies reported a similar mortality rate independently of EF, some authors revealed an intermediate clinical profile and risk between HFpEF and HFrEF, and there is a general agreement in considering the outcome of HFmrEF much more similar to HFpEF (21,22). Despite that CV events are considerably more in HFrEF, prognosis in those with HFmrEF is more strictly related to non-CV events and this tends to balance the overall mortality rate (23).…”
Section: Clinical Characteristics Of Hfmrefmentioning
confidence: 99%